Transforming Education through Gender Mainstreaming: Improving Access and Equity - Fabian Nathaniel Putra Adya; Nicholas Dwi Chandra; Muhammad Fadhil Mansoer; Aniqotul Ummah (Journal of Feminism and Gender Studies, 2025)
Gender mainstreaming is a form of approach with the aim of recognizing and resolving gender inequality and creating equality between women and men. The state of the environment and social life of society is greatly influenced by education, in terms of implementing gender policies in the education sector is a complex and difficult issue. There are many important challenges faced in its implementation, by studying using qualitative methods by conducting literature studies, and this research will involve qualitative methods. Where, gender mainstreaming has stages in its implementation because gender mainstreaming in the education sector itself has several obstacles. With the existence of gender mainstreaming in the education sector, a country can progress by increasing human resources in a country.